The Category of Strangeness in the Jewish Tradition - Szczerbiński, Waldemar (Studia Europaea Gnesnensia, 2024)
The phenomenon of strangeness seems to be a timeless and universal problem. The feeling of alienation was especially experienced by the Jews living in the diaspora. However, the aim of this article is not to discuss the attitude of other nations towards Jews as strangers but, on the contrary, to show the attitude of Jews towards non-Jews in the biblical, rabbinic, modern and contemporary context. The analyses of the category of strangeness seem to be particularly relevant and significant in the context of the ongoing war in Israel.